PERBANDINGAN LATIHAN PLIOMETRIK DEPTH JUMP DAN JUMP TO BOX POWER TERHADAP OTOT TUNGKAI DALAM SMASH PERMAINAN BOLA VOLI - Suprianti, Deswita; Paripurna, Zenda (Jurnal Olahraga, 2017)
This study aims to find out better plyometric exercises between depth jump and jump to box plyometrics exercises on leg muscle power in volleyball smash games in Mts Salafiah extracurricular. This research uses experimental methods with the design of "pretest-posttest one group design". The population in this study were volleyball students in Mts Salafiah extracurricular totaling 30 students. Samples taken from the results of the sampling technique that is purposive sampling, with criteria namely; (1) actively participating in extracurricular activities in Mts Salafiah, (2) registered as extracurricular participants in Mts Salafiah, (3) willing to take part in the training during the research. Based on these criteria, there were 20 students who met them. The instrument used for the jump height test is the vertical jump. Data analysis using t test. The results of the analysis showed that: (1) There was an effect of depth jump plyometric training on leg muscle power in volleyball smash games in Mts Salafiah extracurricular, with t count 3.405> t table 2.23, and significance value 0.008 <0.05, increase in the average difference in value 5.40 cm. (2) There is an effect of jump to box plyometric training on leg muscle power in volleyball smash in Mts Salafiah extracurricular, with t count value 2. 945> t table 2.23, and significance value 0.016 <0.05, increase in mean difference of 3.70 cm. (3) Jump to box plyometric training is better than depth jump plyometric training on leg muscle power in volleyball smash games in Mts Salafiah extracurricular, with an average difference of 10.50 cm